Production of Thin PbxSn1–xTe Films by “Hot Wall” Method for Creating IR-Photodetectors - V. A. Ivanov; V. V. Krasovskii; V. F. Gremenok; L. I. Postnova (Наука и техника)
Alloys of lead and tin telluride (PbxSn1–xTe) are materials with good thermoelectric properties, as well as semiconductors that can be used as long-wave infrared detectors. Polycrystalline telluride of PbxSn1–xTe (0.05 £ x £ 0.80) alloys has been synthesized by direct fusion technique. Thin films of these materials have been obtained by the hot wall method depositing Сorning 7059 on glass substrates at Tsub = (200–350) oC and vacuum of about 10–5 Torr. The microstructure of the films has been investigated by XRD, SEM and EDX methods. The X-ray spectra of thin films have been in satisfactorily agreement with the spectra of the powder target and indicated the absence of binary phases. The films have shown a natural cubic crystalline structure. While increasing the lead content, the unit cell parameter of the crystal also increases. The established linear relationship between the unit cell parameter and the elemental composition corresponds to Vegard's law. The SEM analysis has shown that the films are polycrystalline, have a columnar structure, are tightly packed and have good mechanical adhesion. The grain size depends on the chemical composition and temperature of the substrate. The electrical measurements have shown that the grown films are non-degenerate semiconductors of p-type conductivity. The conductivity of the films was in the range of σ = (3 × 101)–(1 × 104) Ω–1×cm–1. An increase of lead concentration leads to a decrease in electrical conductivity. Hall mobility in the grown thin films increases in the range of changes in the lead content from ~10 to ~23 at. %, and decreases with a further increase to ~33 at. %. At the same time, the strongest dependence of the decrease in mobility on an increase in temperature increase is observed for films with a high lead content and is explained by the predominant scattering of charge carriers by vibrations of the crystal lattice. For a sample with an average lead concentration, an alternative effect of two scattering mechanisms is observed in the temperature dependence of the mobility: by impurity ions and by phonons.